Todas las definiciones son un promedio - Meléndez Acuña, Alfonso; Rodríguez Gómez, Felipe (Escuela Colombiana de Ingeniería Julio Garavito, 2017)
A friend once gave me a cartridge belt that read "Art is more important than math". My first reaction was to write with a "not" marker between "is" and "more". However, the fundamental question was what is "art" and what is "math". The exercise of defining any of the two words is to average conceptions and in this way to restrict. Generally, when asked what art is, most people seek to relate it to techniques such as painting or sculpting, or to concepts such as what is beautiful or aesthetic (whatever that means); However, in the effort of humanity to develop a sense of individual identity, we have begun to confuse even our own definitions. Usually, people associate mathematics with statistics, engineering, science, and restrict their definition of use, excluding everyday life and its wide implementation possibilities.

Una amiga me regaló una vez una cartuchera que decía “Art is more important than math”. Mi primera reacción fue la de escribir con un marcador “not” entre “is” y “more”. Sin embargo, la pregunta fundamental era qué es “art” y qué es “math”. El ejercicio de definir cualquiera de las dos palabras es promediar concepcio-nes y de esta manera restringir. Generalmente, cuando se pregunta qué es arte, la mayoría de las personas buscan relacionarlo con técnicas como pintar o esculpir, o con conceptos como lo que es bello o estético (lo que sea que eso signifique); sin embargo, en el esfuerzo de la humanidad por desarrollar un sentido de la identidad individual, hemos empezado a confundir incluso nues-tras propias definiciones. Por lo regular, la gente asocia las matemáticas con las estadísticas, las ingenierías, las ciencias, y restringen su definición de uso, excluyendo la vida diaria y sus amplias posibilidades de implementación.
Keywords: Promedio; Definiciones; Average; Definitions